COVID-19 and informal settlements – implications for water, sanitation and health in India and Indonesia. Issue 1 (7th September 2020) - Parikh, Priti; Karim, Yasmin Bou; Paulose, Jacob; Factor-Litvak, Pam; Nix, Emily; Aisyah, Dewi Nur; Chaturvedi, Hemant; Manikam, Logan; Lakhanpaul, Monica; ,
Abstract : Informal settlements are home to over 1 billion people worldwide and are characterised by high population densities and poor environmental conditions. The authors identify the impact of COVID-19 on existing water and sanitation practices and potential pathways for the transmission of COVID-19 in informal settlements in India and Indonesia. In the short term, there is an urgent need for mobile and contactless hand washing, washing/bathing facilities and toilets. In the long term, COVID-19 provides an opportunity to invest in centralised water and sanitation networked solutions appropriate for high-density settings to integrate those settlements into cities and improve environmental conditions and health in these cities.